Feline and canine vaccination protocols in Peninsular Malaysia and veterinarian perceptions of the recommendations by the WSAVA Asian vaccination guidelines group - Md tahir, Sameerah Hani (2016)
Vaccination is one of the most important components in the preventive health care for dogs and cats. With new recommendations from the WSAVA Asian VGG on vaccination protocols that are vastly different from long established protocols, there may exist doubts, criticisms and reluctance to adopt these new protocols. This study was carried out to determine the current practices of feline and canine vaccinations in peninsular Malaysia and to understand the perceptions of veterinarians regarding the new protocols. A questionnaire adapted from the WSAVA Asian VGG was used and distributed randomly to private clinics in several states of peninsular Malaysia. 42 clinics participated in this study and 82% (n=34) of veterinarians were familiar with the guidelines. The majority (53.3%, n=17), of clinics recommends starting the puppy vaccination series at the 8th week of age, with the last vaccination recommended at 16th weeks of age (77%, n=25). 100% recommend a booster after one year and 96.8% (n=31) practice annual vaccination following the first year booster. Only 50% (n=16) of the clinics recommend continuing vaccination for senior and geriatric dogs, with 81% (n=16) recommending it annually and 19% (n=6) recommending it triennially. The age of recommendation for the start of the kitten vaccination series is also variable with a majority of veterinarians (85%, n=36) starting it at 8 weeks of age. The last vaccination for the kitten series is recommended at 16 weeks of age (77%, n=32). All clinics practice annual revaccination of adult cats. The perception of veterinarians towards the recommendation varies. 55% (n=23) would consider following the recommended guidelines for the vaccination protocols, only if suitable vaccine products were available. More thorough discussions among veterinarians, researchers, pharmaceutical industries and the regulatory authorities are warranted, including local scientific studies on the duration of immunity (DOI).